생활체육동호인의 자아존중감과 자기결정성이 소비성향, 제품동일시 및 구매행동에 미치는 영향 - 이재우; Jae-woo Lee; 정정희; Jung-hee Jung (Ch'eyuk kwahak yŏn'gu, 2020)
[목적] 이 연구의 목적은 생활체육동호인의 자아존중감과 자기결정성이 과시적 소비, 윤리적 소비, 제품동일시 긍정적 구전 및 재구매의도에 미치는 영향 관계를 구조방정식모형을 통해 실증적으로 분석하는 것이다. [방법] 수도권지역에 소재한 생활체육동호회 9개소의 남녀 회원 279명을 대상으로 하였다. 표본추출은 편의 표본추출법과 설문지작성은 자기평가기입식으로 하였다. 구조모형을 검증하기 위해 SPSSWIN Ver. 23.0과 AMOS 18.0을 사용하였다. [결과] 첫째, 자아존중감은 과시적 소비에 긍정적인 영향을 미쳤다. 둘째, 자기 결정성은 윤리적 소비에 긍정적인 영향을 미쳤다. 셋째, 과시적 소비는 제품동일시에 긍정적인 영향을 미쳤다. 넷째, 윤리적 소비는 제품동일시에 긍정적인 영향을 미쳤다. 다섯째, 제품동일시는 긍정적 구전에 긍정적인 영향을 미쳤다. 여섯째, 제품동일시는 재구매의도에 긍정적인 영향을 미치지 않았다. 일곱째, 긍정적 구전은 재구매의도에 긍정적인 영향을 미쳤다. [Purpose] The purpose of this study was to empirically analyze the relationship between a sports-for-all club members self-esteem and self-determination, conspicuous consumption, ethical consumption, product identification, positive word of mouth & repurchase intention through structural equation model analysis. [Methods] For this purpose, this study set 279 members at the nine sports-for-all club located in national capital region as the research subjects. In an effort to verify the proposed structural model, this study used SPSSWIN Ver. 23.0 and AMOS 18.0. [Results] First, self-esteem had a positive effect on conspicuous consumption. Second, self-determination had a positive effect on ethical consumption. Third, conspicuous consumption had a positive effect on product identification. Fourth, ethical consumption had a positive effect on product identification. Fifth, product identification had a positive effect on positive word of mouth. Sixth, product identification didn’t had a positive effect on repurchase intention. Seventh, positive word of mouth had a positive effect on repurchase intention.